KORUPSI MASA VOC: REFLEKSI SEJARAH DALAM DUNIA PENDIDIKAN UNTUK MEMBANGUN MENTALITAS ANTI-KORUPSI - Sulistiowati, Irma; Nugroho, Aditya Widiadi (Universitas Negeri Malang, 2024)
Abstract:The corruption mentality has long been rooted in the lives of the Indonesian people. From the colonial period until now, corruption is still often found on a small and large scale. From generation to generation they always try to minimize and suppress acts of corruption. One of them is by building anti-corruption mental awareness, as a step to eradicate corruption in Indonesia. The anti-corruption mental development process can be carried out in various ways and media. One of them is through historical education with reflection on the VOC period in Indonesia. Educators can use the discussion method in instilling anti-corruption values. The active involvement of students will provide an overview of how students assess and respond to acts of corruption. It is hoped that students will be able to understand and practice anti-corruption measures in everyday life. This research is qualitative research with a descriptive approach. The method of data collection used the historical heuristic collection method and literature review